Optimizing Planar Antenna Arrays Using Genetic Algorithms for Enhanced Radar Performance in Direction of Arrival Estimation - Methq Kadhum Alnoori; Malik Jasim Farhan; Enas F. Rawashdeh (Journal of Engineering and Sustainable Development)
This paper proposes the optimization of planar antenna arrays for DOA estimation enhancement in radar systems, where accuracy and computational efficiency need to be well balanced. This work describes a new methodology using GAs to obtain an optimal configuration of the antenna elements, allowing a considerable reduction in computational complexity. Using the ESPRIT algorithm for azimuth and elevation angle estimation, the proposed approach achieves an RMSE as low as 0.2 degrees under an SNR of 20 dB. For practical setups, an antenna size configuration of M = 8, N = 3 with 85 snapshots can achieve an optimal tradeoff, reducing the computational cost by 35% compared to conventional methods while maintaining high accuracy. These results substantiate the appropriateness of the methodology for low-power and low-resource embedded radar processors. They will be further enhanced by real-time capability using FPGAs and GPUs for hardware acceleration and improving overall system performance.